Perlawanan Kwee Kek Beng dalam Rubrik Hindia And Holland Dan Djamblang Kotjok Pada Surat Kabar Sin Po (1923-1960) - Jihan Jauhar Nafisah; Andi Suwirta (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This article aims to describe the aspirations of the figure Kwee Kek Beng who is known as an opinion maker in the history of the press movement in Indonesia in 1923-1960. The problem that will be studied in this article is: "How is Kwee Kek Beng's effort in advancing the Sin Po newspaper, especially in Advancing the Sin Po Newspaper with Articles / Rubrics?" In the writing process, the writer uses historical methods in the form of heuristics, source criticism, interpretation, and historiography with an interdisciplinary approach. Based on the research results, in the process of developing the press movement in Indonesia, Kwee Kek Beng managed to become an opinion maker in Indonesia through his various controversial writings. Evidence of this is the exposure of Kwee Kek Beng to a press offense, the banning of the Sin Po newspaper. In his writings, Kwee Kek Beng conveyed various aspirations and concerns of the people towards the government, especially in the years 1923-1960. This shows the importance of the role of the mass media in an effort to voice the voice of the people as part of a means of resistance against colonialism.